An innovative autonomous wheelchair conversion kit - Salma, Yaakub; Alsibai, Mohammad Hayyan (AIP Publishing, 2019)
Independent mobility is very important for human beings for fulfilling their needs. Some people use wheelchairs to improve their limitation in mobility due to their disabilities. However, some wheelchair users cannot use it independently and therefore they might need help from others who are not always available. Therefore, they need an assistive device that able to detect the surrounding environment, choose the path and move along it while avoiding any obstacles. In this paper, an innovative autonomous conversion kit preliminary design is presented. The proposed system contains two main subsystems: Self-positioning and mapping systems. The main problem in autonomous vehicles is accurate localization and accurate heading toward the destination. To improve the accuracy averaging technique is proposed. Moreover, two rotary encoders are used to calculate the rotation of the wheels to make sure the wheelchair can move straight. Moreover, the rotary encoder readings were combined with a compass reading to adjust the rotating angles to be more accurate. Experiments have been conducted on the ability of the system in getting the accurate and precise location. Moreover, the initial ability to find the path to reach the destination is evaluated. Results demonstrate the ability of the wheelchair to move autonomously in the real time.